Estudo da Ritalina® (Cloridrato de Metilfenidato) sobre o sistema nervoso central de animais jovens e adultos: aspectos comportamentais e neuroquímicos - Linhares, Maria Isabel (2012)
Attention-deficit hyperactivity disorder (ADHD) is a prevalent and debilitating disorder diagnosed on the basis in persistent levels of overactivity, inattention and impulsivity. Stimulant drugs have been effective in treating this disorder, and methylphenidate (MPH) is the most widely prescribed therapeutic agent and its use has increased significantly in recent years, however, the consequences of its use are still poorly known. The MFD was assessed in classical animal models to the screening of drugs with activity in anxiety, depression and convulsion, such as elevated plus maze (EPM), open field, rota rod, forced swimming and pilocarpine-induced seizures and a neurochemistry study, through the level of monoamines, such as dopamine (DA), norepinephrine (NE) and 5-hidroxytriptamine (5-HT) but the activity of the enzyme acetylcholinesterase (AChE). The MPH was administered acutely in all tests at doses of 2,5; 5; 10 e 20 mg/Kg, through the oral via (p.o.) in young mice (21 days) and adults. Results showed that the MPH presented an anxyolitic effects in the models of EPM, since increased all the parameters analyzed in the EPM, such as NEOA, PEOA, TPOA, PTOA, at doses of 10 and 20 mg/Kg in young animals, and only in animals of 20 mg/Kg in adults. In the open field, we observed an increase in locomotor activity at all doses in young animals and only at higher doses (10 e 20 mg/Kg) in adult animals. Not was observed no alteration the number of rearing and grooming. MPH presented antidepressant effect of Central Nervous System (CNS), since in the forced swimming, decreases the time of immobility in doses of 10 and 20 mg/Kg in young animals and only at a dose of 20 mg/Kg in adult animals. The neurochemistry evaluation comproved the antidepressant effect do MPH, because there was an increased concentration of monoamines. The test of the seizure by pilocarpine, MPH did decrease the latency of convulsion and latency of death in young and adult animals, suggesting that the MPH has proconvulsivante activity. The study of the effects of the cholinergic neurotransmission system has show that pretreatment with MPH reduced AChE activity only in the striatum. In conclusion, these effects showed that MPH presented anxiolitic effect, antidepressant effect and proconvulsivante activity.